A study and design of standing wheelchair. (2022) - Merai, Sushant; Shah, Denish; Trivedi, Bhavinkumar; Joshi, Poojan; Kushwah, Sagarsingh
Abstract: Currently, there are more than 700 million people in the globe who are disabled or handicapped in a certain way. Most European and Asian nations and all civilized countries have seen their senior population expand at an alarming rate during the previous few decades. The scientific world has been paying more attention to this problem in recent years, and numerous solutions have been presented to help people in these groups live more independently. To counter such problems, the instrument or the machine named wheelchair was invented which is currently going under various changes to increase the ease and comfortability of the patient or a disabled person. The current study proposes a standing wheelchair that is fully mechanized. To operate the wheelchair, it is attached to both a fixed frame and a mobile frame that moves back and forth. On one side, the belt is fixed to the moving frame and rotates on a pulley on the fixed frame. To convey force, a chain drive is used. Thus, the design and development of such a wheelchair with its results are demonstrated in the current paper. In addition, a comprehensive study of four materials was done which includes Mild Steel, Aluminum, Titanium, and Carbon Fiber on the parameters such as material characteristics, weight, and economical aspects. Based on the study, a standing wheelchair is designed and fabricated works better for the physically disabled person.